Engineering ethics education and engineering practice: A study from a small island with an impressively high number of engineering programs - Atasoylu, Emine (American Society for Engineering Education 1818 N Street, N.W. Washington D.C 20036-2479, 2007)
This paper describes engineering ethics education in universities of Cyprus (both North and South) and the impact of engineering ethics education on engineering practice. In the first phase of this study, we conducted a detailed review and analysis of curricula, elective courses and their course descriptions. Data was also collected from the national higher education accreditation bodies, the deans of faculty in the schools of engineering, and the program chairs of the respective universities targeted in this study. In the second phase, we surveyed graduates of these engineering programs on engineering ethics education, code of ethics, awareness and knowledge of how to address ethical issues. We compared the responses of those who had received an engineering ethics course or seminar during their undergraduate engineering education to those who had not. The results were consistent with the assertion made by the Accreditation Board for Engineering and Technology (ABET) that engineering curricula should include courses in engineering ethics. As a result of this study, an action has been suggested which targets provision of short courses or periodic seminars to increase awareness and to teach the skills on how to prevent and how to deal with ethical issues, especially for those who haven't previously received any training in engineering ethics. Another outcome of the study reflected that the difference in cultural norms and laws in Cyprus might be yet another reason necessitating professional ethics education. © American Society for Engineering Education, 2007.
114th Annual ASEE Conference and Exposition, 2007 --
Keywords: Curricula; Professional aspects; Social aspects; Technical presentations; Engineering ethics education; Ethical issues; Engineering education